A facile synthesis of 3-amino-2,5-dihydropyridazines and 4-deazatoxoflavin analogues via [3+3] atom combination - Abdelmoniem, Amr Mohamed; Ghozlan, Said Ahmed Soliman; Butenschön, Holger; Abdelhamid, Ismail Abdelshafy (European Journal of Chemistry, 2016)
Michael addition reactions of arylhydrazone derivatives with different functionalized α-cyanoacrylamides were conducted and yielded new pyridazine-4-carboxamide compounds. A further reaction with acetic anhydride was investigated resulting in the formation of a 4-deazatoxoflavin analogue. A one step synthesis of 4-deazatoxoflavin was also carried out by reacting azaenamine with N-carbamoyl-2-cyano-3-phenylacrylamide to give deazatoxoflavin. Unambiguous structural elucidation was done using 2D-HMBC spectroscopy.